2021
DOI: 10.1007/jhep09(2021)104
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear extensions of gravitating dyons: from NUT wormholes to Taub-Bolt instantons

Abstract: Recent work has shown the existence of a unique nonlinear extension of electromagnetism which preserves conformal symmetry and allows for the freedom of duality rotations. Moreover, black holes and gravitational waves have been found to exist in this nonlinearly extended electrovacuum. We generalise these dyonic black holes in two major ways: with the relaxation of their horizon topology and with the inclusion of magnetic mass. Motivated by recent attention to traversable wormholes, we use this new family of T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…However, when both electric and magnetic charges are present, already static spherical solutions feature 'small' deviations from the corresponding solutions of the Maxwell theory, e.g. [15,16] (see also [16,17] for the case of Taub-NUT solutions). On the other hand, the presence of slow rotation reveals the full non-linearity of the theory [18] and the full rotating solution is currently unknown.…”
Section: Theories Of Nle and The Modmax Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, when both electric and magnetic charges are present, already static spherical solutions feature 'small' deviations from the corresponding solutions of the Maxwell theory, e.g. [15,16] (see also [16,17] for the case of Taub-NUT solutions). On the other hand, the presence of slow rotation reveals the full non-linearity of the theory [18] and the full rotating solution is currently unknown.…”
Section: Theories Of Nle and The Modmax Theorymentioning
confidence: 99%
“…Interestingly, there is already a small catalogue of such solutions. Namely, it was shown that the spherically symmetric [15,16] and the Taub-NUT [16,17] solutions in the ModMax theory are (although slightly different from those of Maxwell) remarkably 'Maxwell-like', though this is no longer true in the presence of slow rotation [18].…”
Section: Introductionmentioning
confidence: 99%
“…As we observed in [5], this class of conformal electrodynamics includes (after a constant rescaling of the gauge potential A m ) the conformal and duality-invariant ModMax theory. More recently, investigations similar to those of [6] but specific to ModMax have been carried out and further extended in [7][8][9][10] (see also [11][12][13]).…”
Section: Jhep10(2021)031mentioning
confidence: 99%
“…Also effects of the modified Maxwell electrodynamics (5.1) on properties and thermodynamics of black holes (e.g. Taub-NUT and Reissner-Nordström ones), and gravitational waves have been explored in a number of papers [76,79,[103][104][105][106][107][108]. Here I will restrict the discussion only to the simplest example of the Reissner-Nordström black hole.…”
Section: Modmax Effects On Black Holesmentioning
confidence: 99%